2002
DOI: 10.1046/j.1525-1438.2002.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of p53, bcl-2, and p21WAF1/CIP1 in early cervical carcinoma: Correlation with clinical outcome

Abstract: The objective of this study was to assess the value of p53, bcl-2, and p21(WAF1/CIP1) immunoreactivity as predictors of pelvic lymph node metastases (LNM), recurrences, and death due to the disease in early stage (FIGO I-II) cervical carcinomas. FIGO stage, type of histopathology, and tumor grade were also evaluated in this series of patients treated by radical hysterectomy (Wertheim-Meigs) between 1965 and 1990. A total of 172 patients were included. A tumor was regarded as positive when more than 30% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
(39 reference statements)
1
16
1
Order By: Relevance
“…p53-positive immunostaining is unexpected and may be caused by TP53 gene mutation or abnormal accumulation of an inefficient p53 protein in the absence of gene mutation (22). We have observed high p53 positivity in all groups, which corroborates its possible role in cervical carcinogenesis; however, p53 did not prove to be a good biomarker for distinguishing low-from high-grade lesions, as previously reported (24,25). However, this has not been the findings in many studies (7,9,23).…”
contrasting
confidence: 49%
“…p53-positive immunostaining is unexpected and may be caused by TP53 gene mutation or abnormal accumulation of an inefficient p53 protein in the absence of gene mutation (22). We have observed high p53 positivity in all groups, which corroborates its possible role in cervical carcinogenesis; however, p53 did not prove to be a good biomarker for distinguishing low-from high-grade lesions, as previously reported (24,25). However, this has not been the findings in many studies (7,9,23).…”
contrasting
confidence: 49%
“…Cervix Cancer. Several reports, 18,[72][73][74][75][76][77][78][79] have addressed the significance of bcl-2 overexpression to treatment outcome for cervix cancer with similar disparity (Table 5) as reported for apoptotic index in Table 1.…”
Section: Assessment Of Apoptotic Cells ("Apoptotic Index")mentioning
confidence: 89%
“…Studies of p21 expression in cervical cancer have reported higher levels of expression of p21 in cancer tissue compared to normal tissue [28,29], while others showed there is no association between the expression of p21 and the pathological features of cervical cancer [30]. After infection with HPV, the E6 protein of HPV promotes p53 degradation and thus inhibits p21 expression and function.…”
Section: Discussionmentioning
confidence: 99%